1983
DOI: 10.1007/bf00397331
|View full text |Cite
|
Sign up to set email alerts
|

Reactions in chloroplasts, cytoplasm and mitochondria of leaf slices under osmotic stress

Abstract: The effect of osmotic dehydration on metabolic reactions in three different subcellular compartments (chloroplast, cytoplasm and mitochondria) was studied in vacuum-infiltrated thin leaf slices from various plants, in the absence of stomatal control. The reactions tested were CO2 fixation in the light (chloroplast), CO2 fixation in the dark (cytoplasm), and O2 uptake in the dark (mitochondria). In most plants, the sensitivity of dark CO2 fixation to dehydration was similar to the sensitivity of photosynthesis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

1985
1985
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…The decrease in chlorophyll content might be attributed to the increased degradation of chlorophyll pigments due to stress-induced metabolic imbalance (Ashraf et al 1994). In addition, high osmotic pressure generated under stress has been suggested to create an interference with the de novo synthesis of the structural components of chlorophyll (Kaiser et al 1983). Although, at present, the underlying mechanisms of priming-mediated response is not clear, the results certainly demonstrated the positive effect of seed priming in improving the growth of seedlings under NaCl/ PEG stress.…”
Section: Discussionmentioning
confidence: 76%
“…The decrease in chlorophyll content might be attributed to the increased degradation of chlorophyll pigments due to stress-induced metabolic imbalance (Ashraf et al 1994). In addition, high osmotic pressure generated under stress has been suggested to create an interference with the de novo synthesis of the structural components of chlorophyll (Kaiser et al 1983). Although, at present, the underlying mechanisms of priming-mediated response is not clear, the results certainly demonstrated the positive effect of seed priming in improving the growth of seedlings under NaCl/ PEG stress.…”
Section: Discussionmentioning
confidence: 76%
“…In the light of this differential hyperaccumulation property of A. halleri shoots, it is of interest to determine the actual leaf tissue tolerance level of A. halleri in comparison to its metal‐sensitive relative A. thaliana . The leaf slice method is an efficient and simple test for effectors because of the easy and defined application technique and has been used, for example, in studying the effect of osmotic dehydration on carbon fixation (Kaiser et al ., 1983) and is also useful in analysing changes in leaf gene expression (Horling et al ., 2002; A. Kandlbinder et al ., unpublished). Tissue tolerance tests for hydrophilic compounds such as heavy metals cannot be adequately performed with intact leaves, because metal permeability through the cuticle and stomates is low and difficult to control and the intratissue distribution undefined.…”
Section: Discussionmentioning
confidence: 99%
“…Boyer and Younis (9) suggest that increased Mg2e concentration in the dehydrated stroma inhibits photosynthesis. Kaiser (15,17) has presented correlative evidence supporting a hypothesis that stromal volume reduction upon dehydration increases the K+ concentration, which then inhibits photosynthesis. Berkowitz and Gibbs (4, 5) have indicated that upon dehydration, stromal pH is too low to support optimal photosynthesis, and that raising the stromal pH partially reverses this inhibition.…”
mentioning
confidence: 89%